African life with known and unknown love partners - Moshikaro, Asaph (Cambridge Scholars Publishing, 2018)
This book explores the issues of promiscuity and carelessness and their effect on the prevalence of STIs and HIV/AIDS in Africa from a perspective focusing on African cultural constructs. As such, it puts African sexual habits and cultural beliefs vis-à-vis the STI and HIV/AIDS debate in an understandable context. It will appeal to both the general public, as well as people in the private and public health spheres concerned with this scourge, as the book will assist in dealing with the associational and causative factors of the STI and HIV/AIDS epidemic.